Synthesis of new 1,3,4-oxadiazole and benzothiazolylthioether derivatives of 4-arylmethylidene-3-substituted-isoxazol-5(4H)-one as potential antimycobacterial agents - Chavan, Abhijit P.; Deshpande, Rujuta R.; Borade, Nandkumar A.; Shinde, Abhijit; Mhaske, Pravin C.; Sarkar, Dhiman; Bobade, Vivek D. (Medicinal Chemistry Research, 2019)
A new series of 4-[(substituted benzylidene)-3-[(5-(pyridine-4-yl)-1,3,4-oxadiazole-2-ylthio)-methyl]i soxazol-5(4H)-one (6a-g) and 4-(substituted benzylidene)-3-((benzo[d]thiazol-2-ylthio)methyl)isoxazol-5(4H)-one (8a-g) was synthesized. All the synthesized compounds were screened for antitubercular activity against Mycobacterium tuberculosis H37Ra (ATCC 25177) and Mycobacterium bovis BCG (ATCC 35743) and antibacterial activity against Escherichia coli (NCIM 2576), Pseudomonas flurescence (NCIM 2059), Staphylococcus aureus (NCIM 2602), Bacillus subtilis (NCIM 2162). Amongst the synthesized 1,3,4-oxadiazole and benzothiazoyl thioether derivatives, compounds 6b and 8b showed excellent antimycobacterial activity and compounds 6b, 8a, 8b, and 8d showed excellent antibacterial activity against all tested antibacterial strains. The synthesized compounds were further evaluated for their cytotoxic activity against the HCT 116 and HeLa cancer cell lines. The 1,3,4-oxadiazole and benzothiazoyl thioether derivatives 6a-g and 8a-g did not show cytotoxicity.
Keywords: 1; 3; 4-Oxadiazole; antibacterial activity; Antitubercular activity; Benzothiazol; Isoxazol-5(4H)-one; Thioeteher